Electrically Excited Plasmonic Ultraviolet Light Sources. Issue 24 (2nd May 2021) - Ahmadivand, Arash
Abstract: The emission of photons from metal‐insulator‐metal (MIM) nanojunctions through inelastic tunneling of electrically driven electrons is a well‐acknowledged approach to develop miniaturized light sources and ultradense photonic instruments. Generally, the existing research in the optimization of electromigrated tunneling junctions is principally centered on the generation of visible and near‐infrared lights. This study reports on the near‐ultraviolet (NUV, λ ≈ 355 nm) light emission from enhanced tunneling of electrons using aluminum nanoelectrodes. Compared to conventional noble metals, the high electron density and low screening of aluminum enable supporting of pronounced local fields at high energies (i.e, ultraviolet (UV)). As the color of light can be straightforwardly determined by the properties of tunneling structures, the exquisite features of aluminum have empowered the fashioning of tunneling devices that are able to effectively sustain plasmons at short wavelengths and emit UV light with high photon yield. This demonstration is a breakthrough in the generation of high‐energy beams using electrically excited aluminum tunneling platforms, which promisingly accelerates the implementation of electrically tunable and ultradense UV light sources. Abstract : The emission of near‐ultraviolet photons from aluminum‐insulator‐aluminum nanojunctions through inelastic tunneling of electrically driven electrons is analyzed, assessed, and demonstrated. Via both theoretical studies and experimental measurements, the operating mechanism and radiation properties of the developed tunneling instrument are investigated and discussed. Beyond that, the radiation efficiency, photon‐yield, and quantum efficiency of the platform are quantified and evaluated.